2020
DOI: 10.1103/physrevb.101.104410
|View full text |Cite
|
Sign up to set email alerts
|

Microwave dynamics of the stoichiometric and bond-disordered anisotropic S=1 chain antiferromagnet NiCl24SC(NH2

Abstract: We studied electron spin resonance in a quantum magnet NiCl2-4SC(NH2)2, demonstrating a field-induced quantum phase transition from a quantum-disordered phase to an antiferromagnet. We observe two branches of the antiferromagnetic resonance of the ordered phase, one of them has a gap and the other is a Goldstone mode with zero frequency at a magnetic field along the four-fold axis. This zero frequency mode acquires a gap at a small tilting of the magnetic field with respect to this direction. The upper gap was… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…We showed that the dependence ∆(h) in the linear spin-wave approximation is drastically different from the one which includes quantum corrections of the order 1/S. The latter are responsible for nonmonotonic dependence of ∆(h) on the external magnetic field which was observed experimentally in both DTN 21 and DTNX 22 . Furthermore, according to our analysis quantum corrections give rise to nontrivial ∆(h) dependence on the system parameters in contrast to the simple classical behaviour.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…We showed that the dependence ∆(h) in the linear spin-wave approximation is drastically different from the one which includes quantum corrections of the order 1/S. The latter are responsible for nonmonotonic dependence of ∆(h) on the external magnetic field which was observed experimentally in both DTN 21 and DTNX 22 . Furthermore, according to our analysis quantum corrections give rise to nontrivial ∆(h) dependence on the system parameters in contrast to the simple classical behaviour.…”
Section: Discussionmentioning
confidence: 79%
“…One can see that at fixed J a = 0.2 K ∆ min increases with J c increase and decreases with D increase. Finally, we want to stress that our analysis explains the fact that ESR spectrum of DTN can remain almost unchanged 22 when small concentrations of Br are introduced, while according to the neutron experiment exchange couplings and single-ion anisotropy constant increase with the increase of Br concentration 18 . From the point of view of ∆ (1) (h) in our theory different system parameters variation can compensate each other, which can not occur in the linear spin-wave approximation.…”
Section: Comparison With Experimentsmentioning
confidence: 85%
See 3 more Smart Citations